Biologically active filtration for fracturing flowback and produced water treatment. (August 2017) - Freedman, Daniel E.; Riley, Stephanie M.; Jones, Zackary L.; Rosenblum, James S.; Sharp, Jonathan O.; Spear, John R.; Cath, Tzahi Y.
Graphical abstract: Highlights: Biologically active filtration was studied as a pretreatment for UF and NF. Biologically active filters can be acclimated to treat saline O&G wastewater. BAF can remove >90% organic matter from produced water. Abstract: Reclamation of fracturing flowback and produced water associated with unconventional oil and gas resource development is becoming a more widely applied management practice because it protects freshwater resources through elimination of surface discharge and by reducing demand for high quality water sources. Reduction of organic matter has been a notable wastewater treatment challenge and has limited practical opportunities for reuse of these waste streams. This research focuses on harnessing the ability of microorganisms to biodegrade organic carbon present at high concentrations in flowback and produced water. Bench-scale and lab-scale biofiltration systems were investigated to determine adaptability of biofilms and measure biodegradation of organic carbon under different operating conditions. Microorganisms associated with biologically active carbon filters were initially acclimated to a produced water stream from the Piceance Basin. Following successful acclimation, the bench-scale system consistently achieved more than 90% dissolved organic carbon removal (Co ∼ 240 mg/L). Similar performance was observed for the lab-scale system, demonstrating system scalability. After treating distinct wastewater feeds (produced water [Co ∼ 350 mg/L] and flowback water [Co ∼ 2150 mg/L] from the Denver-Julesburg Basin), the system further demonstrated robustness and flexibility. Results from the performance evaluation validated the ability of the system to maintain treatment efficiency under variable operating conditions, including different pretreatment, aeration rates, temperatures, and empty-bed contact times.